华北克拉通对前寒武纪超大陆旋回的基本制约 - 李江海; 侯贵廷; 黄雄南; 张志强; 钱祥麟 (岩石学报, 2001)
全球大陆克拉通在前寒武纪至少记录了 3次超大陆聚合 -裂解的构造旋回。不同大陆前寒武纪地质的研究证明 ,板块构造模式可以前推至新太古代。超大陆的聚合表现为大规模造山带的穿时性发育 ,而裂解则表现为大陆裂谷系、非造山花岗岩及巨型基性岩浆岩省的同期快速发育。广泛的区域地质研究揭示华北克拉通前寒武纪地质构造演化具有明显的阶段性差异特征 ,克拉通主体形成于新太古代陆壳增生与碰撞造山过程。华北克拉通在太古宙末期首次经历强烈的裂解作用 ,在古元古代晚期涉及强烈的陆缘再造作用。在古元古代末期发生第二次大规模的裂解活动 ,随后以中元古代末期的造山带拼合为Rodinia超大陆的组成部分。详细的区域构造对比证明 . At least three supercontinental cycles with assembly and breakup are documented for the Precambrian continental blocks. As demonstrated by more and more regional geological research of the world, the plate tectonics has been operated since the Neoarchean. The tectonic assembly and formation of supercontinents were commonly associated with the diachronous development of orogenic belts, whereas the breakup episodes were characterized by the rapid occurrences of continental rift, anorogenic granites and large mafic igneous province. The widespread regional geological studies demonstrate that the geological and tectonic evolution of North China Block(NCB) can be divided into some distinct stages. It mainly finished its cratonization in the Neoarchean through accretionary and collisional orogenies, rather than simply homogeneous crustal growth. The NCB underwent extensive break-up at the end of the Neoarchean(2.50 similar to 2.40 Ga), followed by tectonothermal reworking along its continental margins in the late Paleoproterozoic(2.20 similar to 1.90Ga). The second breakup episode occurred in the NCB at about 1.85 similar to 1.70Ga. The late Mesoproterozoic orogenic belt along the southern margin of NCB led to the finial assembly of NCB with Rodian. As indicated by the regional tectonic correlation, the NCB has dose geological-tectonic relation in the Precambrian with the Baltica, Eastern Antarctica, Southern India, South America continental blocks. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000168457600001&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 SCI(E) 中文核心期刊要目总览(PKU) 中国科学引文数据库(CSCD) 23 02 177-186 17